Outcome and postoperative complications in 73 dogs with thyroid carcinoma with gross vascular invasion managed with thyroidectomy. (4th June 2021) - Latifi, Max; Skinner, Owen T.; Spoldi, Elisa; Ackerman, Leah; Souza, Carlos H. De M.; Yoon, Jin; Vinayak, Arathi; Tuohy, Joanne L.; Wallace, Mandy L.; Dornbusch, Josephine A.; Selmic, Laura E.; Menard, Jenna; et al.
Abstract: Excellent outcomes have been reported following thyroidectomy for thyroid carcinoma in dogs, but outcomes for thyroid carcinomas with gross vascular invasion are poorly described. This study describes the clinical outcomes and complications in dogs with thyroid carcinomas with gross vascular invasion undergoing thyroidectomy. Medical records of dogs that underwent thyroidectomy between January 1st 2010 and December 31st 2019 were reviewed at 10 hospitals. Signalment, diagnostic data, primary and adjuvant treatments performed, and outcome were abstracted. Survival was calculated using Kaplan–Meier analysis. Multiple logistic regression was used to identify variables associated with disease‐specific survival. Seventy‐three dogs were included, of which 58 underwent unilateral thyroidectomy and 15 underwent bilateral thyroidectomy. Complications were reported in five dogs (three major, two minor; 6.8%) intraoperatively and 12 dogs (two major leading to death, 10 minor; 16.4%) postoperatively. Seven (9.6%) dogs developed locoregional recurrence at a median of 238 days postoperatively (range: 15–730 days). Distant metastasis was suspected or confirmed in nine dogs (12.3%) at a median of 375 days postoperatively (range: 50–890 days). Twenty‐seven dogs (37%) received adjuvant therapy (chemotherapy: n  = 21; radiotherapy: n  = 6). Thirty‐nine dogs were euthanized or died, with 20 deaths related to disease ( n  = 10) or of unknown cause ( n  = 10), 19 due to unrelated causes, and nine lost to follow‐up. Median overall and disease‐specific survival were 621 days and not reached respectively. One‐year disease‐specific survival rate was 82.5%. No variables were associated with disease‐specific survival in our dataset. Surgery may be considered for loco‐regional therapy in dogs with thyroid carcinoma with gross vascular invasion.